Implementasi Visi dan Misi dalam Membentuk Siswa Berakhlaqul Karimah di Sekolah Menengah Kejuruan al-Ikhlas Kaliboto Tarokan Kediri - Ahmad Ali Riyadi; Achmad Choliq; Khoiriyah Khoiriyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
The context in this research; first, how is the formulation of the vision and mission at SMK Al Ikhlas Kaliboto Tarokan. Second, how is the implementation of the school's vision and mission in forming students with good morals at SMK Al Ikhlas Kaliboto Tarokan Kediri. The method used in this research is a qualitative approach, with the type of case study research. To obtain the data, the writer used the method of participant observation, interviews, and documentation. This research produces findings: 1). The practice of formulating the vision and mission at SMK Al Ikhlas Tarokan is good because it is based on the needs of the surrounding community and contains a statement of ideals, short, realistic, attractive, easy to remember, easy to trace beliefs. and does not leave the characteristics of the school. 2) Implementation of the school's vision and mission in the formation of akhlaqul karimah at Al Ikhlas Tarokan Vocational School in the Islamic boarding school environment using exemplary methods, advice, motivation, punishment, giving gifts, habituation, supervision, going well and carried out by all teachers, mostly is a boarding school alumnus.